Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7150/jca.25926
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Modulates Cell Cycle Progression to Enhance Tumour Cell Proliferation through AKT/FOXO1 Signalling in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a disease with an extremely poor prognosis that is characterized by a rich extracellular matrix (ECM). Tenascin-C (TNC) is a component of the ECM and plays a role in tumour progression. In this study, we reported that TNC is overexpressed in PDAC tissues and is correlated with tumour stage and cyclin D1 expression. Cyclin D1 is key regulator of the cell cycle G1/S transition. Further experiments revealed that TNC promotes G1/S transition through AKT signalling. TNC/AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The results of in vitro studies further confirmed our conclusion. Previous researches demonstrated that increasing FOXO1 level could lead to cell cycle G1 arrest in kinds of tumor cells [45,46]. Liu and colleagues also revealed that overexpression of FOxO1 caused cell cycle G1 arrest of mesangial cells of rat kidney [47].…”
Section: Discussionmentioning
confidence: 98%
“…The results of in vitro studies further confirmed our conclusion. Previous researches demonstrated that increasing FOXO1 level could lead to cell cycle G1 arrest in kinds of tumor cells [45,46]. Liu and colleagues also revealed that overexpression of FOxO1 caused cell cycle G1 arrest of mesangial cells of rat kidney [47].…”
Section: Discussionmentioning
confidence: 98%
“…For example, Akt activation induces GSK3b/cyclinD1-mediated cell proliferation [ 49 ]. Akt signaling was shown to downregulate p27, a cyclin-dependent kinase inhibitor that induces cell cycle arrest [ 50 ]; in contrast, attenuation of Akt function conversely increases p27-suppressed cancer cell growth [ 51 ]. We found that AA significantly suppressed the pAkt levels, indicating that AA is a promising compound for further research and development.…”
Section: Discussionmentioning
confidence: 99%
“…We used western blotting to explore the mechanism by which OGD mediates the progression of CI/R in vitro . As shown in Figure 5A – 5C , OGD upregulated protein expression of FOXO1 and p27 Kip1, the cell cycle mediator [ 14 ], in HT22 cells, while this phenomenon was suppressed in the presence of miR-27a-3p mimics. Moreover, flow cytometric analysis confirmed that OGD induced G1 arrest in HT22 cells, while overexpression of miR-27a-3p partially reversed the effect of OGD on cell cycle distribution ( Figure 5D , 5E ).…”
Section: Resultsmentioning
confidence: 99%